Self-Control Capacity Moderates the Effect of Stereotype Threat on Female University Students’ Worry During a Math Performance Situation - Bertrams, Alex; Lindner, Christoph; Muntoni, Francesca; Retelsdorf, Jan (Frontiers in Psychology, 2022)
Stereotype threat is a possible reason for difficulties faced by girls and women in the fields of science, technology, engineering, and mathematics. The threat experienced due to gender can cause elevated worry during performance situations. That is, if the stereotype that women are not as good as men in math becomes salient, this stereotype activation draws women’s attention to task-irrelevant worry caused by the fear of conforming to the negative stereotype. Increased worry can reduce cognitive resources, potentially leading to performance decrements. We argue that such worry is more pronounced immediately after an unrelated self-control demand, which is assumed to temporarily decrease people’s self-control exertion over their attention and stream of thought (i.e., relatively low self-control capacity). This prediction was examined in an experiment conducted with 102 participating university students enrolled in courses in which math plays a crucial role. After the manipulation of self-control capacity (low vs. high), stereotype threat was induced for the female students, but not the male students. Then, the students were asked to report their thoughts during a math performance situation (i.e., written thought protocols) three times. Multiple-group autoregressive path models revealed that when self-control capacity was relatively low, female compared with male students reported more intense worry in the initial two thought protocols. In contrast, in the relatively high self-control capacity condition, female and male students did not differ significantly in their reported worry at any time. These results expand on previous findings, suggesting that threat effects depend on definable situational self-control conditions.